Effects of small-scale farmers’ perception of financial Literacy on financial capital investment in Soy Sub- Location Kakamega County - Agura, S. (Strathmore University, 2025)
Smallholder farmers play a vital role in food security and economic development, yet their ability to make informed financial capital investment decisions remains limited due to varying levels of financial literacy. This study examined the effects of smallholder farmers’ perception of financial literacy on financial capital investment in Soy Sub-location, Kakamega County. Guided by the Push-Pull Theory and the Theory of Planned Behavior, and anchored in a pragmatic research philosophy, the study explored how perceptions of interest rate fluctuations, investment risk diversification, and inflation influenced investment decisions. A descriptive correlational research design was employed, utilizing both structured questionnaires and interview guides to collect data from 331 randomly selected smallholder farmers. The findings indicated that the perception of investment risk diversification had a significant positive effect on financial capital investment, suggesting that farmers who understood and applied diversification principles were more likely to allocate their resources effectively. The perception of interest rate fluctuations also had a significant positive effect, though its influence was comparatively lower, reflecting limited responsiveness to interest rate changes. In contrast, the perception of inflation had a significant negative effect, meaning that anticipated or actual inflation discouraged farmers from committing long-term financial investments. Correlation analysis confirmed significant positive relationships between the financial literacy components and financial capital investment. Multiple linear regression results showed that a substantial proportion of the variation in financial capital investment was explained by the independent variables. The study concluded that financial literacy perception significantly influenced financial capital investment decisions, with investment risk diversification playing the most impactful role. The study recommended the strengthening of financial literacy training programs, expanding access to financial advisory services, and promoting collaboration between financial institutions and agricultural cooperatives to support well-informed investment decisions. Future research could assess the long-term impact of financial literacy interventions on the economic resilience and investment behavior of smallholder farmers. Key words: Financial literacy, smallholder farmers, investment risk diversification, interest rates, inflation, financial capital investment, Kakamega County.
Full - text thesis